Pengaruh Pengakuan Pendapatan dan Pengaruhnya terhadap Laporan Keuangan : Studi Kasus pada PT. Asuransi Jiwa BNI Jiwasraya - Djanegara, H. Moermahadi Soerja (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2005)
In company practice acknowledgement of income is implemented by using basic accrual method. This has to be done by the company in order to cover its whole obligation. The income of PT Asuransi BNI Jiwasraya consists of two kinds, underwriting income and non-underwriting income. Both kinds of income are obtained from the companyâs activity which triggers equity increase and is not gained from capital investment. The financial report of an insurance company is very much influenced by assumption factor so that the acknowledgement of income will influence the financial report. Its purpose is to inform the stake holders and to meet the qualitative character. Key words : Revenue Recognition; Financial Report.